Penetapan Kadar Fenolik Ekstrak Etanol Biji Alpukat (Persea americana Mill.) Menggunakan Metode Spektrofotometri UV-Vis - Taufiqurrahman Majid; Rais Razak; Zainal Abidin (BULLET : Jurnal Multidisiplin Ilmu, 2023)
Avocado (Persea americana Mill.) is a plant that grows in tropical and sub-tropical climates, so it is very easy to grow in Indonesia. The use of avocado (Persea americana Mill.) as a medicinal plant has been widely used. People usually use avocado seeds as traditional medicine. The efficacy obtained is thought to be due to the presence of various phenolic compounds in the plant. This study aims to determine the phenolic content of ethanol extract in the seeds of avocado (Persea americana Mill.). Phenolic compounds in avocado seeds were extracted using the maceration method with ethanol solvent. The phenolic content was determined using the UV-visible spectrophotometry method with Follin-Ciocalteau reagent and gallic acid was used as a comparison. The results showed that the average phenolic content of ethanol extract of avocado seeds was 13.150 mg GAE/g extract.